Fish Community Structure Of The Bahu River Estuary Manado City: - Sampe, Ayumi Angraini; Manu, Gaspar D.; Kambey, Alex D.; Pratasik, Silvester Benny; Rondonuwu, Arie B.; Rangan, Jety K. (Jurnal Ilmiah Platax, 2024)
Community structure is an ecological term to indicate what organisms are present in a given environment, in what numbers, and how they are interconnected, through ecological indices that reflect dominance, evenness, and richness traits. The estuary is the most downstream part of the river and is connected to the sea. The Bahu River estuary is a habitat for a variety of aquatic life, especially fish, where water quality conditions greatly affect the abundance, diversity, and dominance. The methods used in this study were general field survey methods and fishing methods using the "swept area" method (Sparre & Venema, 1998). Data collection was carried out based on the time of collection using beach seine gear. This research was conducted with several stages, namely fishing in the field which will become data, data analysis and discussion. The results of this study indicate the composition of fish species in the Bahu River Estuary there are 11 families, 11 genus, and 14 species with a total of 86 individuals. The results of data analysis of the highest relative abundance in the Bahu River Estuary were in June, namely the Ambassis urotaenia species with a value of 45.90%. The results showed the community structure in the Bahu River Estuary in June and July (H' = 1.53 - 1.64, J' = 0.64 - 0.79, D = 0.31 - 0.26). Keywords: Diversity; Evenness; Dominance; River Estuary.